2020
DOI: 10.3390/atmos11090951
|View full text |Cite
|
Sign up to set email alerts
|

Behaviors of Chromium in Coal-Fired Power Plants and Associated Atmospheric Emissions in Guizhou, Southwest China

Abstract: Coal burning is a main concern for a range of atmospheric pollutants, including the environmentally sensitive element chromium (Cr). Cr migrates to the environment through stack emissions and can leach out from solid coal-burning byproducts, thereby causing adverse effects on the ecosystem. In this study, atmospheric emissions of Cr from six coal-fired power plants (CFPPs), as well as the distribution of Cr inside these CFPPs in Guizhou Province, Southwest China, were investigated. Among the six CFPPs, one was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…Following the explication by Clarke ( 1993 ) and Meij et al ( 2004 ), Cr in coals could be categorized as an element between nonvolatile and semi-volatile and was mainly retained in solid wastes after coal combustion. Researchers have reported that air pollution control devices (APCDs) in CFPPs had remarkable impacts on the partitioning of Cr in solid wastes (Li et al, 2020 ). This paper compared the Cr concentrations in different solid wastes from CFPPs in China over recent years, and presented them in detail in Table 5 .…”
Section: Environmental Impacts Of Cr Associated With Cfppsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following the explication by Clarke ( 1993 ) and Meij et al ( 2004 ), Cr in coals could be categorized as an element between nonvolatile and semi-volatile and was mainly retained in solid wastes after coal combustion. Researchers have reported that air pollution control devices (APCDs) in CFPPs had remarkable impacts on the partitioning of Cr in solid wastes (Li et al, 2020 ). This paper compared the Cr concentrations in different solid wastes from CFPPs in China over recent years, and presented them in detail in Table 5 .…”
Section: Environmental Impacts Of Cr Associated With Cfppsmentioning
confidence: 99%
“…As shown in Table 5 , compared with the feed coal, Cr was enriched in the fly ash and bottom ash after coal combustion, whereas existed less in the flue gas desulfurization (FGD) gypsum. For most CFPPs, a higher Cr concentration in fly ash could be observed, and the reasons for this phenomenon were described as follows: (1) in comparison with bottom ash, fly ash had smaller particle size and stronger adsorption capacity for the condensation of Cr (Han et al, 2021 ; Tang et al, 2013 , 2022b ), (2) the occurrence of Cr in coals was an important influencing factor for its redistribution in solid wastes, and Cr in the form of organic/sulfide combinations was more likely to partially evaporate and thus coagulate on the fly ash (Fu et al, 2019 ; Li et al, 2020 ). In summary, the solid wastes from CFPPs needed to be carefully disposed to prevent their possible mobilization into the environment.…”
Section: Environmental Impacts Of Cr Associated With Cfppsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trace elements in the Earth's surface system are critical to livestock wellbeing due to their biological functions or toxicities [1]. The abundance of trace elements in the ambient environment is affected by both natural and anthropogenic sources [2,3]. In modern society, human activities are more extensive than at any previous time in the Earth's history and have deeply influenced the biogeocycling of trace metals [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Trace elements, contained in coal, migrate with coal combustion products. In one study, atmospheric emissions of Cr from six coal-fired power plants (CFPPs), as well as the distribution of Cr inside these CFPPs, were measured in Guizhou Province, Southwest China [8]. The results showed that Cr in the feed fuel of these CFPPs ranged from 39.5 to 101.5 mg•kg −1 (average: 68.0 ± 24.8 mg•kg −1 ) and was approximately four times higher than the national and global average.…”
mentioning
confidence: 99%